2018
DOI: 10.4102/sajpsychiatry.v24i0.1222
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic stress disorder among the staff of a mental health hospital: Prevalence and risk factors

Abstract: BackgroundMental health service providers are frequently exposed to stress and violence in the line of duty. There is a dearth of data concerning the psychological sequelae of the frequent exposure to stress and violence, especially among those who work in resource-limited countries such as Botswana.AimTo determine the prevalence and predictors of post-traumatic stress disorder (PTSD) among mental health workers in a tertiary mental health institute in Botswana.SettingThe study was conducted in Sbrana Psychiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 23 publications
3
37
0
Order By: Relevance
“…Although the scale demonstrated adequate internal consistency [ 88 ], its other psychometric properties such as factorial validity and norms remain unestablished in the literature. Studies outside the scope of this review [ 116 , 117 , 118 ] have examined mental health professionals’ traumatic experiences using standardised scales such as PTSD Checklist-Civilian Version (PCL-C) [ 119 ] or PTSD Checklist for DSM–5 (PCL-5) [ 120 ]. No study included in the present review used either of the two checklists or some other standardised scale or questionnaire, thereby compromising the accurate measurement of workplace trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Although the scale demonstrated adequate internal consistency [ 88 ], its other psychometric properties such as factorial validity and norms remain unestablished in the literature. Studies outside the scope of this review [ 116 , 117 , 118 ] have examined mental health professionals’ traumatic experiences using standardised scales such as PTSD Checklist-Civilian Version (PCL-C) [ 119 ] or PTSD Checklist for DSM–5 (PCL-5) [ 120 ]. No study included in the present review used either of the two checklists or some other standardised scale or questionnaire, thereby compromising the accurate measurement of workplace trauma.…”
Section: Discussionmentioning
confidence: 99%
“…There is certainly a need for follow-up after incidents, but also for checking whether more support is needed after a week or two. In addition to post-incident trauma counselling, pre-placement personality evaluation of health workers prior to being assigned to psychiatric units may be beneficial [56].…”
Section: Discussionmentioning
confidence: 99%
“…In the same category were CI descriptions of four cases of sexual harassment, and situations where patients took hostages to get medicine or to get their own way in Serious assault (50) Anxious/aggressive/disruptive patient (38) Death threats, including against family (34) Threats with/possession of any object/weapon (32) Sexual harassment (4) Taking hostages 3Threats/violence against co-patients/relatives (21) Violent acts towards others than staff Self-harm/suicide attempt (15) Staff aggression/violence 3Active defence/intervention (70) Ways the staff responded Ways in which staff dealt with aggressive situations and the eventual outcome Alarm/call for help (56) Call for police/fire brigade (31) Passive defence/de-escalation (30) Patient discharged from the ward 1Mechanical restraint 69Ways in which the incident ended Delimiting/supervising (46) Calming down of patient/ebbing of situation (42) Removal from the ward (35) Enforced medication (31) Anaesthetising/rapid tranquillisation of the patient (5)…”
Section: Details Of Violent and Aggressive Acts And Situationsmentioning
confidence: 99%
“…Previous studies reported PTSD rates up to ten-fold higher among emergency service workers with respect to the general population [ 5 ]. Particularly, PTSD rates range between 10% and 21% among medical doctors and nurses [ 6 , 7 ]. A recent meta-analysis on 18 studies including over 30,000 subjects showed PTSD in 11% of ambulance personnel [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different factors were found to predispose health workers to PTSD or burnout. From a socio-demographic perspective, being a young, female, nurse with low professional education levels are considered negative factors [ 2 , 6 , 14 ]. For what concerns organizational work factors, employee reward systems, peer and manager support, besides well-designed organizational structures improve resilience to stressful and traumatic events experienced on duties [ 15 ].…”
Section: Introductionmentioning
confidence: 99%